Anammox bacterial abundance and diversity in different temperatures of purple paddy soils by 13C-DNA stable-isotope probing combined with high-throughput sequencing - Yu, Zijie; He, Xinhua; Li, Zhitong; Zhou, Shuang; Guo, Dalu; Pu, Hao; Luo, Hongyan (Frontiers in Microbiology, 2023)
Anaerobic ammonium oxidation (anammox) plays a vital role in the global nitrogen cycle by oxidizing ammonium to nitrogen under anaerobic environments. However, the existence, abundance, and diversity of anammox bacteria between different temperatures are less studied, particularly in purple paddy soils. 13C-DNA stable-isotope probe combined with Illumina MiSeq high-throughput sequencing was employed to research soil abundance and diversity of anammox bacteria. In doing so, 40-60 cm depth soils from typical purple paddy soils in Chongqing, southwest China, were cultured under 12CO2-labeled and 13CO2-labeled at 35 °C, 25 °C, 15 °C, and 5 °C for 56 days. The results showed that anammox bacteria were not labeled by 13CO2 at 5 °C. The highest abundance of anammox bacteria was found at 25 °C (3.52×106~3.66×106 copies·g-1 dry soil), followed by 35 °C and 15 °C (2.01×106~2.37×106 copies·g-1 dry soil) and almost no increase at 5 °C. The relative abundance of Candidatus Jettenia sp. was higher at 25 °C and 15 °C, while Candidatus Brocadia sp. was higher at 35 °C and 5 °C. This study reveals differences in the anammox bacteria between different temperatures in purple paddy soils. Results from this study could provide implications for a better understanding of soil nitrogen cycling regulated by anammox bacteria.